Analisis Korelasi Walking Permeability dan Walking Effort (Studi Kasus Terminal di Kota Bandung) - Nur Rahmawati, Octaviani; Gabriela Palupi, Adriana; Yuwani Nadhifa, Salma Yuwani Nadhifa (Institut Teknologi Bandung, 2024)
Abstract Bandung was chosen as a pilot area for Indonesian Mass Transit (MASTRAN) project to increase urban mobility and accessibility. With this MASTRAN project, public transportation nodes should be accessible by all modes, one of which is walking. However, in urban areas in Indonesia, walking activities are still not an option. According to some studies, this is caused by the lack of walking infrastructure and environment feasibility. Therefore, the quality of pedestrian infrastructure and environment must be improved to make these public transportation nodes easy for pedestrians to reach. In this case, walking permeability and walking effort assessment are chosen as tools to assess the pedestrian walkability. By doing these assessments, it is found that Kiaracondong Station has the largest average WPDI and WPTI values with values of 1.48 and 1.90 respectively. In addition, it is found that The South Bandung Station has the biggest walking effort index which value is 1.66. By analyzing both assessments, it can be concluded that the increase of WPDI tends to increase WPTI. Besides, it also can be concluded that stations have higher time increments than bus terminals due to an increase in the distance required for pedestrian access to the main terminal entrance.